2013
DOI: 10.1186/1471-2458-13-732
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular risk factors and socioeconomic level among public-sector workers in Angola

Abstract: BackgroundCardiovascular diseases are the leading cause of death in the majority of developed and developing countries. African countries are currently facing an increase in both cardiovascular and transmitted diseases. In addition, cardiovascular risk varies among different socioeconomic groups. Thus, we determined the prevalence of modifiable cardiovascular risk factors in apparently healthy public-sector workers and investigated possible relationships with socioeconomic status.MethodsWe employed a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
6
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 30 publications
4
39
6
3
Order By: Relevance
“…This is reinforced when we observe that in a study conducted approximately 10 years ago the prevalence of obesity was significantly lower than in the current (3.2% vs 20%), and there were no individuals with Grade III obesity 15. In this study, overweight and obesity were higher in women, which is in accordance with another study in the country,17 and the global trend;49 and was associated with a higher rate of high BP, as is traditionally reported 50…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is reinforced when we observe that in a study conducted approximately 10 years ago the prevalence of obesity was significantly lower than in the current (3.2% vs 20%), and there were no individuals with Grade III obesity 15. In this study, overweight and obesity were higher in women, which is in accordance with another study in the country,17 and the global trend;49 and was associated with a higher rate of high BP, as is traditionally reported 50…”
Section: Discussionsupporting
confidence: 90%
“…In relation to BMI, the combined prevalence of overweight and obesity was 54.29%, which is relatively higher than that of previous studies,15,17 suggesting a trend to increase in prevalence of weight-related problems. This is reinforced when we observe that in a study conducted approximately 10 years ago the prevalence of obesity was significantly lower than in the current (3.2% vs 20%), and there were no individuals with Grade III obesity 15.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…A study in China showed the higher risk of metabolic syndrome in women with lower education and monthly income, but male subjects did not reveal this relationship (8). Moreover, some studies that were conducted about the relationship between cardiovascular diseases and socioeconomic status reported a higher prevalence of cardiovascular disease in developed countries (9)(10)(11). It seems that the study of the relationship between the socioeconomic factors and metabolic syndrome, cardiovascular disease or diabetes in developing countries has a great importance because these countries experience nutritional transition.…”
Section: Introductionmentioning
confidence: 99%